Beneficial effects of intravenous iron therapy in a rat model of heart failure with preserved systemic iron status but depleted intracellular cardiac stores - Aleksandra Paterek (Nature Portfolio, 2018)
Abstract Iron deficiency (ID) commonly occurs in chronic heart failure (HF) and is associated with poor prognosis. Neither its causes nor pathophysiological significance are clearly understood. We aimed to assess iron status and the effect of iron supplementation in the rat model of post-myocardial infarction (MI) HF. Four weeks after induction of MI to induce HF or sham surgery, rats received intravenous iron (ferric carboxymaltose) or saline, 4 doses in 1-week intervals. HF alone did not cause anemia, systemic or myocardial ID, but reduced myocardial ferritin, suggesting depleted cardiomyocyte iron stores. Iron therapy increased serum Fe, ferritin and transferrin saturation as well as cardiac and hepatic iron content in HF rats, but did not increase myocardial ferritin. This was accompanied by: (1) better preservation of left ventricular (LV) ejection fraction and smaller LV dilation, (2) preservation of function of Ca2+ handling proteins in LV cardiomyocytes and (3) reduced level of inflammatory marker, CRP. Furthermore, iron supplementation did not potentiate oxidative stress or have toxic effects on cardiomyocyte function, but increased activity of antioxidant defenses (cardiac superoxide dismutase). Despite lack of systemic or myocardial ID we found evidence of depleted cardiomyocyte iron stores in the rat model of HF. Furthermore we observed positive effect of iron supplementation and confirmed safety of iron supplementation in this setting.